PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Ernawati, Dewi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
A company through its financial manager should beable to run its function in managing finance properly and as efficient as possible. The standard which is used to assess the success of a financial managerin managing the finance of the company is from the firm value. The firm value can reflect the condition of the company. There are many factors which can determine the firm value. This research is conducted to test the influence of profitability, leverage, and firm size to the firm value on the manufacturing companies which are engaged in the field of consumer goods industry which are listed in Indonesia Stock Exchange.The samples are 22 manufacturing companies which are engaged in the field of consumer goods industries which are listed in Indonesia Stock Exchange. The sample collection technique has been carried out by using purposive sampling technique. The data is the secondary data. The data analysis has been carried out by using classic assumption test, the multiple regressions analysis and the hypothesis test which is done by using t test and F test with the level of significance 5% are used as the data analysis technique.The result of the analysis shows that profitability has positive influence to the firm value, with the significance value 0.000 is smaller than Î± = 0.05 and the regressions coefficient is 0,074. The leverage has negative influence to the firm value, with the significance value 0.097 is bigger than Î± = 0.05 and the regressions coefficient is -1.641. The firm size has positive influence to the firm value with the significance value 0.000 is smaller than Î± = 0.05 and the regressions coefficient is 0.353. Â Keywords: Profitability, Leverage, Firm Size and Firm Value.